The Influence of Entrepreneurship Education, Peer Influence, and Self-Efficacy on Students' Entrepreneurial Intentions - Nurjanah, Dheananda Larasyati; Harsono, Harsono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The intention to engage in entrepreneurship among students needs to be examined starting from now to understand students' careers after graduating from school. This research aims to analyze and identify the influence of entrepreneurship education, peer influence through self-efficacy on students' entrepreneurial intentions. The research method employs a quantitative approach with data collection through distributing questionnaires via Google Forms, measuring four variables: entrepreneurship education, peer influence, self-efficacy, and entrepreneurial intentions. The population in this research consists of students majoring in Financial Accounting at State Vocational High School 1 Surakarta, and the research sample is obtained using purposive sampling with a total of 100 students from class X1 Financial Accounting as respondents. Hypotheses are tested using the Structural Equation Model (SEM) approach based on Partial Least Square (PLS) using SmartPLS 4.0 software. This research yields results indicating that entrepreneurship education, mediated by self-efficacy, significantly influences students' entrepreneurial intentions. However, peer influence does not have a significant effect on students' entrepreneurial intentions.